2014
DOI: 10.11648/j.ajhr.20140206.18
|View full text |Cite
|
Sign up to set email alerts
|

Health System in Bangladesh: Challenges and Opportunities

Abstract: The health system of Bangladesh relies heavily on the government or the public sector for financing and setting overall policies and service delivery mechanisms. Although the health system is faced with many intractable challenges, it seems to receive little priority in terms of national resource allocation. According to the World Health Organization (WHO 2010) only about 3% of the Gross Domestic Product (GDP) is spent on health services. However, government expenditure on health is only about 34% of the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
154
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(159 citation statements)
references
References 11 publications
4
154
0
1
Order By: Relevance
“…Due to the high OPP, thousands of poor households are being pushed into poverty every year which is called catastrophic expenditure. Studies have shown that 6.4 million (4%) people in Bangladesh get poorer every year due to excessive health cost 21,22 . People have to borrow money or sell assets to pay for health care.…”
Section: Healthcare Financing Featuresmentioning
confidence: 99%
“…Due to the high OPP, thousands of poor households are being pushed into poverty every year which is called catastrophic expenditure. Studies have shown that 6.4 million (4%) people in Bangladesh get poorer every year due to excessive health cost 21,22 . People have to borrow money or sell assets to pay for health care.…”
Section: Healthcare Financing Featuresmentioning
confidence: 99%
“…The World Bank's World Development Indicators: Health System (2013) shows a similar status in Bangladesh. According to this report and other studies (such as Islam and Biswas, 2014), from 2006 to 2011, there were only 0.4 physicians and 0.2 nurses per 1,000 population in Bangladesh, whereas in Australia, there were 3.9 physicians and 9.6 nurses, and the World averages were 1.4 physicians and 2.9 nurses per 1,000 population. Furthermore, the World Bank found a significant gap between sanctioned and filled health worker positions in Bangladesh.…”
Section: Bangladesh and Its Health Sectormentioning
confidence: 50%
“…The Bangladesh Health Watch Report (BHWR, 2008) notes that qualified modern practitioners account for a small proportion of the entire workforce, making up just 5% of all health care providers with just 7.7 physicians, dentists and nurses together per 10,000 population (BHWR, 2008: ii). The recent reviews of the Bangladesh health system (Islam and Biswas, 2014;Khan et al 2015;Darkwa et al 2015;Khatun et al 2015) echo the similar critical shortage of professional health workforces. All of these recent studies confirm that there is no significant change in the number of the professional health workforce in recent time in Bangladesh.…”
Section: Bangladesh and Its Health Sectormentioning
confidence: 98%
See 2 more Smart Citations